Murder by mistake - Heley, Veronica (Heley, Veronica. Ellie Quicke mysteries., 2010)
Ellie Quicke is still inclined to act hastily, despite husband Thomas' steadying influence. When she took in a young rape victim, she knew the commitment might become a burden, but she didn't expect it to become an invitation to further violence. Mia's best friend Ursula is eager to help, but has a wedding to plan - as does Ellie's daughter Diana. Both want Ellie to stage their receptions. Can Ellie keep Mia safe? Can she pull off two weddings, when one would be havoc enough? And can she wear the same outfit to both?